Factors of the Formation of Modern Energetic Reality in North Western Europe - Gudmundsson, Fe Amor Parel; Prosekov, Sergey; Sokolinskaya, Natalia; Tarakanov, Sergey; Lopatin, Evgeniy (International Journal of Energy Economics and Policy, 2020)
The paper proposes the radical transformation of the global energy market is influenced by a combination of geopolitical, macroeconomic, technological realities, the combination of which leads to fundamental changes in the world order in the development of the gas segment. The paper uses the method of energy balance. It proved ensuring growth in gas production and transportation, production and sale of high value-added gas products in the domestic, European and Asian markets. The onset of the Golden Age of Gas, according to the forecast of the International Energy Agency (IEA), is expected by 2035, when global gas consumption will increase by one and a half times. The study result is that the expansion of the range of gas resources and the modernization of the structure of the gas industry, the formation of the latest Eurasian energy architecture in the face of increasing competition in international markets necessitate the strengthening of Russia’s leading positions in the global gas market. Keywords: North Western Europe, strategy, union, partnership, forecasting JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.9392